The Nuclearization of South Asia - Matinuddin, Kamal (New York Oxford University Press, 2002)
This study traces the nuclear and missile programmes of India and Pakistan from their inception, and discusses their present status. It highlights the security models of both the adversaries and focuses on the nuclear weapons programme of both the nations, examining the role of outside powers.
Include appendix, index
Keywords: Nuclear weapons -- South Asia -- Military policy -- Pakistan